Evaluation of the Utility of Bone Marrow Morphology and Ancillary Studies in Pediatric Patients Under Surveillance for Myelodysplastic Syndrome. Issue 6 (5th April 2018) - Chisholm, Karen M; Xu, Min; Davis, Billy; Ogi, Amy; Pacheco, M Cristina; Geddis, Amy E; Tsuchiya, Karen D; Rutledge, Joe C
Abstract: Objectives: To evaluate the utility of flow cytometry, karyotype, and a fluorescence in situ hybridization (FISH) panel in screening children for myelodysplastic syndrome (MDS). Methods: Bone marrow morphology, flow cytometry, karyotype, and FISH reports from 595 bone marrow specimens (246 patients) were analyzed. Results: By morphology, 8.7% of cases demonstrated at least unilineage dysplasia and/or increased blasts. Flow cytometry identified definitive abnormalities in 2.8% of cases, all of which had abnormal morphology. Of the 42 cases (7.2%) with acquired karyotypic abnormalities, 26 had no morphologic dysplasia. With a 98.2% concordance between karyotype and MDS FISH, FISH only identified two additional cases, both with low-level (<4%) abnormalities. Peripheral blood count evaluation only identified the absence of thrombocytopenia to correlate with an absence of abnormal ancillary tests. Conclusions: The combination of morphologic evaluation and karyotype with judicious use of flow cytometry and MDS FISH is sufficient to detect abnormalities for these indications.